Off- and on-target effects of genome editing in mouse embryos - Shinya AYABE; Kenichi NAKASHIMA; Atsushi YOSHIKI (The Society for Reproduction and Development, 2018)
Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas-based genome editing technology has enabled manipulation of the embryonic genome. Unbiased whole genome sequencing comparing parents to progeny has revealed that the rate of Cas9-induced mutagenesis in mouse embryos is indistinguishable from the background rate of de novo mutation. However, establishing the best practice to confirm on-target alleles of interest remains a challenge. We believe that improvement in editing strategies and screening methods for founder mice will contribute to the generation of quality-controlled animals, thereby ensuring reproducibility of results in animal studies and advancing the 3Rs (replacement, reduction, and refinement).